Identification and Characterisation of Entomopathogenic Microbes: An Innovative Science Learning Resource to Improve Student Science Literacy on the Topic of Agricultural Biotechnology - Arfan Arfan; Ratnawati Ratnawati; Hasmari Hasmari (Postgraduate, University of Mataram, 2025)
The challenge in science education is to connect biotechnology concepts with real-world contexts and local potential. This study aims to explore and identify local entomopathogenic microbes as innovative learning resources on the topic of agricultural biotechnology, specifically biological control of onion pests. This exploratory study includes field surveys in the onion centre of Guntarano Village and laboratory analysis. Isolation of entomopathogenic fungi from infected Liriomyza spp. larvae was carried out using the insect bait method. The isolates obtained were purified, identified based on morphological characteristics (macroscopic and microscopic), and their spore density was calculated. The exploration successfully screened six potential fungal isolates. Morphological identification revealed the presence of Aspergillus flavus, Aspergillus niger, Trichoderma sp., and one isolate suspected to be Metarhizium sp. All isolates had high spore densities (> 10⁷ conidia/mL), with the Metarhizium sp. (Larva 4) and A. niger (Larva 2) isolates showing the highest densities. The diversity of entomopathogenic microbes found has the potential to be a source of biopesticide learning in science education. This material can be utilised to develop modules, worksheets, or learning media based on local potential to enhance science literacy and students' understanding of agricultural biotechnology